Effects of curcumin on retinal oxidative stress and inflammation in diabetes - Kanwar Mamta; Kowluru Renu A (Nutrition & Metabolism, 2007)
Abstract Background Oxidative stress and inflammation are implicated in the pathogenesis of retinopathy in diabetes. The aim of this study is to examine the effect of curcumin, a polyphenol with antioxidant and anti-inflammatory properties, on diabetes-induced oxidative stress and inflammation in the retina of rats. Methods A group of streptozotocin-induced diabetic rats received powdered diet supplemented with 0.05% curcumin (w/w), and another group received diet without curcumin. The diets were initiated soon after induction of diabetes, and the rats were sacrificed 6 weeks after induction of diabetes. The retina was used to quantify oxidative stress and pro-inflammatory markers. Results Antioxidant capacity and the levels of intracellular antioxidant, GSH (reduced form of glutathione) levels were decreased by about 30–35%, and oxidatively modified DNA (8-OHdG) and nitrotyrosine were increased by 60–70% in the retina of diabetic rats. The levels of interleukin-1β (IL-1β) and vascular endothelial growth factor (VEGF) were elevated by 30% and 110% respectively, and the nuclear transcription factor (NF-kB) was activated by 2 fold. Curcumin administration prevented diabetes-induced decrease in the antioxidant capacity, and increase in 8-OHdG and nitrotyrosine; however, it had only partial beneficial effect on retinal GSH. Curcumin also inhibited diabetes-induced elevation in the levels of IL-1β, VEGF and NF-kB. The effects of curcumin were achieved without amelioration of the severity of hyperglycemia. Conclusion Thus, the beneficial effects of curcumin on the metabolic abnormalities postulated to be important in the development of diabetic retinopathy suggest that curcumin could have potential benefits in inhibiting the development of retinopathy in diabetic patients.